2023
DOI: 10.1111/cpr.13439
|View full text |Cite
|
Sign up to set email alerts
|

Microglial transglutaminase 2 deficiency causes impaired synaptic remodelling and cognitive deficits in mice

Abstract: Microglia are the primary source of transglutaminase 2 (TGM2) in the brain; however, the roles of microglial TGM2 in neural development and disease are still not well known. The aim of this study is to elucidate the role and mechanisms of microglial TGM2 in the brain. A mouse line with a specific knockout of Tgm2 in microglia was generated. Immunohistochemistry, Western blot and qRT‐PCR assays were performed to evaluate the expression levels of TGM2, PSD‐95 and CD68. Confocal imaging, immunofluorescence staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…[ 47 ] Studies show that deletion of TGM2 in microglia leads to impaired synaptic pruning and cognitive impairment and exacerbates pathological damage in AD in mice. [ 48 ] In the single-cell analysis conducted in this study, it was observed that AFF1 exhibited significant expression in microglia, indicating its potential role in enhancing synaptic remodeling and cognitive function through the upregulation of TGM2 levels, specifically in microglia. Furthermore, the single-cell analysis also revealed significant expression of AFF1 in immune cells and fibroblasts, primarily observed in individuals with CKD.…”
Section: Discussionmentioning
confidence: 83%
“…[ 47 ] Studies show that deletion of TGM2 in microglia leads to impaired synaptic pruning and cognitive impairment and exacerbates pathological damage in AD in mice. [ 48 ] In the single-cell analysis conducted in this study, it was observed that AFF1 exhibited significant expression in microglia, indicating its potential role in enhancing synaptic remodeling and cognitive function through the upregulation of TGM2 levels, specifically in microglia. Furthermore, the single-cell analysis also revealed significant expression of AFF1 in immune cells and fibroblasts, primarily observed in individuals with CKD.…”
Section: Discussionmentioning
confidence: 83%
“…In the postnatal developing brain, the absence of microglial EED, a Polycomb protein vital for synaptic pruning, led to the upregulation of phagocytosis-related genes [ 92 ]. Contrariwise, the deletion of microglial Tgm2 in mice resulted in the downregulation of microglial phagocytic-related genes accompanied by synaptic pruning and cognitive impairment [ 93 ]. A P2RX7-induced proliferation of embryonic spinal cord microglia was proposed after comparison of wild-type and P2rx7 -/- embryos.…”
Section: Molecular Cues Orchestrating Microgliogenesismentioning
confidence: 99%